2014
DOI: 10.1111/mmi.12737
|View full text |Cite
|
Sign up to set email alerts
|

LeuO enhances butyrate‐induced virulence expression through a positive regulatory loop in enterohaemorrhagic Escherichia coli

Abstract: SummaryEnterohaemorrhagic Escherichia coli (EHEC) causes bloody diarrhoea and other severe symptoms such as haemorrhagic uraemic syndrome. The expression of virulence genes on the locus for enterocyte effacement (LEE) and associated genes is regulated by a variety of factors, including transcriptional regulators and environmental signals. Butyrate, one of the major short-chain fatty acids present in the intestine, enhances expression of LEE genes and flagella biosynthesis genes in EHEC O157:H7, resulting in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…Our study did not reveal an obvious change in average daily feed intake, average daily gain, and the feed/gain ratio between the sodium butyrate and control groups, but sodium butyrate exerted a significant effect on ameliorating diarrhea. Sodium butyrate has been shown to relieve diarrhea caused by weaning stress or enterohemorrhagic Escherichia coli in piglets [19][20][21]. Moreover, butyrate therapy is beneficial in patients with congenital chloride diarrhea [22,23], consistent with our results.…”
Section: Discussionsupporting
confidence: 81%
“…Our study did not reveal an obvious change in average daily feed intake, average daily gain, and the feed/gain ratio between the sodium butyrate and control groups, but sodium butyrate exerted a significant effect on ameliorating diarrhea. Sodium butyrate has been shown to relieve diarrhea caused by weaning stress or enterohemorrhagic Escherichia coli in piglets [19][20][21]. Moreover, butyrate therapy is beneficial in patients with congenital chloride diarrhea [22,23], consistent with our results.…”
Section: Discussionsupporting
confidence: 81%
“…However, the detailed mechanism of this regulation is yet to be unravelled. In EHEC, exposure to the levels of butyrate found in the colon increases the expression of the EHEC T3SS through post-transcriptional activation of the transcriptional regulator Lrp 42 . Exposure to the concentrations of acetate and propionate that are found in the small intestine does not significantly affect the virulence of EHEC.…”
Section: Utilization Of Nutrientsmentioning
confidence: 99%
“…LTTRs namely QseA, LeuO and LrhA regulates the LEE genes and the flagellar regulon, and is involved in the microcolony formation and adherence to the epithelial cells20212223. To determine if ribavirin could inhibit LEE genes expression, expression of the target genes ler , a master regulator of LEE and escU in the in vitro cultures of EPEC was quantified by qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…LTTR family proteins, such as QseA21, LeuO23 and LrhA22 regulate the locus for enterocyte effacement (LEE), which is critical for intestinal colonization and pathogenesis of EPEC and EHEC. Although we failed to identify the LTTR protein which was inhibited by ribavirin, we found that the drug inhibits the expression of LEE genes and colonization of mouse small intestine by EPEC.…”
Section: Discussionmentioning
confidence: 99%